Legal Protection for Victims of Domestic Violence - Sarjono Sarjono (Estudiante Law Journal, 2023)
The purpose of this research is to find out what is becomingfactors causing violence against women in the household as well as legal protection efforts for victims of violence against women in the household in the Kusambi Police Region, West Muna Regency. The research method used is Empirical. Legal protection efforts that can be given to victims of domestic violence in the Kusambi Police area from the perspective of police victimology in minimizing the incidence of victims of domestic violence in the Kusambi Police area are carried out using a preventive approach, which is a follow-up effort from pre-emptive efforts. which provides counseling and outreach to the community. Meanwhile, repressive efforts are by way of law enforcement against perpetrators of domestic violence in accordance with applicable punishments. ConclusionFrom the point of view of critical victimology, the main factors that cause violence against women contain three points, namely in terms of substance, constraints by law enforcement officials, and the legal culture of society. Forms of legal protection that can be given to victims of domestic violence in the Kusambi Police area from a victimological perspectivenamely preventive efforts andrepressive.